Understanding mechanical behavior and reliability of organic electronic materials. (2nd February 2017) - Kim, Jae-Han; Lee, Inhwa; Kim, Taek-Soo; Rolston, Nicholas; Watson, Brian L.; Dauskardt, Reinhold H.
Abstract: Abstract : The mechanical properties of organic electronic materials and interfaces play a central role in determining the manufacturability and reliability of flexible and stretchable organic electronic devices. The synergistic effects of mechanical stress and deformation, together with other operating parameters such as temperature and temperature cycling, and exposure to solar radiation, moisture, and other environmental species are particularly important for longer-term device stability. We review recent studies of basic mechanical properties such as adhesion and cohesion, stiffness, yield behavior, and ductility of organic semiconducting materials, and their connection to underlying molecular structure. We highlight thin-film metrologies to probe the mechanical behavior, including when subjected to simulated operational conditions. We also report on strategies for improving reliability through interface engineering and tailoring material chemistry and molecular structure. These studies provide insights into how these metrologies and metrics inform the development of materials and devices for improved reliability.